Diffuse enterochromaffin-like (ECL) cell hyperplasia and multiple gastric carcinoids: a complication of pernicious anaemia. Issue 3 (March 1981) - Hodges, J R; Isaacson, P; Wright, R
Abstract : A man with long-standing pernicious anaemia developed multiple gastric carcinoid tumours with a background of diffuse enterochromaffin-like cell hyperplasia. There is evidence that enterochromaffin-like cells synthesis and store histamine and that their proliferation is stimulated by high serum gastrin levels. Gastric carcinoid tumours can be difficult to differentiate from the more common adenocarcinomas and may be a more frequent complication of pernicious anaemia than is currently recognised.